DAMPAK PERIKLANAN YANG INFORMATIF TERHADAP KEPUTUSAN PEMBELIAN PRODUK SABUN MANDI - Suharno, Rizki Adi Anggoro; Dirgantara, I Made Bayu (Faculty of Economics and Business Diponegoro University, 2018)
This research was conducted to test and analyze causal relationship between Informational Advertising to Consumer Purchase Decision of Toiletries Product, Soap. The aim of this research is also to analyze the difference of information given by advertising to consumer purchase decision of soap product, whether the information of soap product that have been given to the participants can influence the relationship between informational advertising with consumer purchase decision of soap product.The method used in this research is true experimental design with laboratory experiment. The number of participants used was 30 participants, consisting of 15 participants for the experiment group that received the information of the soap product and 15 participants for the control group who did not get the information of the soap product. The data analysis tests used in this research are Paired Sample T-test and Independent Sample T-test in order to know the difference and compare the results between the experimental research groups.The result of the analysis with t-test shows that experiment done successfully. T-test shows that there is a difference in purchase decision of the participant just right before and after treatment with product information applied. The statistical result showed that H1 is accepted. The statistical result also showed that soap information that participant received through an advertisement is capable in providing information needed by the participant to consider and decide their purchase decision about the soap product.